Quality of obstetric care in the sparsely populated sub-arctic area of Norway 2009-2011 - Norum, Jan; Heyd, Anca Kriemhilde; Hjelseth, Bente; Svee, Tove Elisabeth; Mürer, Fred A; Erlandsen, Randi; Vonen, Barthold (BMC Pregnancy and Childbirth, 2013)
Background: It is challenging to obtain high quality obstetric care in a sparsely populated area. In the subarctic region of Norway, significant distances, weather conditions and seasonable darkness have called for a decentralized care model. We aimed to explore the quality of this care. Methods: A retrospective study employing data (2009–11) from the Medical Birth Registry of Norway was initiated. Northern Norwegian and Norwegian figures were compared. Midwife administered maternity units, departments at local and regional specialist hospitals were compared. National registry data on post-caesarean wound infection (2009–2010) was added. Quality of care was measured as rate of multiple pregnancies, caesarean section, post-caesarean wound infection, Apgar score < 7, birth weight < 2.5 kilos, perineal rupture, stillbirth, eclampsia, pregnancy induced diabetes and vacuum or forceps assisted delivery. There were 15,586 births in 15 delivery units. Results: Multiple pregnancies were less common in northern Norway (1.3 vs. 1.7%) (P = 0.02). Less use of vacuum (6.6% vs. 8.3%) (P = 0.01) and forceps (0.9% vs 1.7%) (P < 0.01) assisted delivery was observed. There was no difference with regard to pregnancy induced diabetes, caesarean section, stillbirth, Apgar score < 7 and eclampsia. A significant difference in birth weight < 2.5 kilos (4.7% vs. 5.0%) (P < 0.04) and perineal rupture grade 3 and 4 (1.5% vs. 2.3%) (P < 0.02) were revealed. The post-caesarean wound infection rate was higher (10.5% vs. 7.4%) (P < 0.01). Conclusion: Northern Norway had an obstetric care of good quality. Birth weight, multiple pregnancies and post-caesarean wound infection rates should be further elucidated.